2016
DOI: 10.1038/mtna.2016.6
|View full text |Cite
|
Sign up to set email alerts
|

DNA as Tunable Adaptor for siRNA Polyplex Stabilization and Functionalization

Abstract: siRNA and microRNA are promising therapeutic agents, which are engaged in a natural mechanism called RNA interference that modulates gene expression posttranscriptionally. For intracellular delivery of such nucleic acid triggers, we use sequence-defined cationic polymers manufactured through solid phase chemistry. They consist of an oligoethanamino amide core for siRNA complexation and optional domains for nanoparticle shielding and cell targeting. Due to the small size of siRNA, electrostatic complexes with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…A step‐by‐step extension of a single siRNA revealed that a prolongation of up to 181 DNA nucleotides results in a significant improvement of transfection efficacy (Figure a). This could also be confirmed when using the cationic polymer linear PEI as a transfection agent, which is in good agreement with previous findings showing enhanced activity of linear PEI when using sticky siRNA . The stabilizing effect of the siRNA modification ideally lasts throughout the delivery process where polyplex stability is critical but should not hinder the cytosolic release of the cargo.…”
Section: Nucleic Acid Binding—the Polyplex Formation Processsupporting
confidence: 90%
See 4 more Smart Citations
“…A step‐by‐step extension of a single siRNA revealed that a prolongation of up to 181 DNA nucleotides results in a significant improvement of transfection efficacy (Figure a). This could also be confirmed when using the cationic polymer linear PEI as a transfection agent, which is in good agreement with previous findings showing enhanced activity of linear PEI when using sticky siRNA . The stabilizing effect of the siRNA modification ideally lasts throughout the delivery process where polyplex stability is critical but should not hinder the cytosolic release of the cargo.…”
Section: Nucleic Acid Binding—the Polyplex Formation Processsupporting
confidence: 90%
“…Another strategy to stabilize siRNA polyplexes is the conversion of single siRNA molecules into larger polyanions by hybridization, chemical ligation, click‐chemistry, and coformulation with pDNA, or other polyanions. Our group recently used DNA oligomers as adaptors to increase the size and charge of siRNA to form more stable polyplexes and thus boost transfection efficacies . Several DNA/siRNA nanostructures ranging from DNA extension of one siRNA up to structures with two to ten siRNA units were merged, and polyplexes were formed with a 3‐arm sequence‐defined oligomer.…”
Section: Nucleic Acid Binding—the Polyplex Formation Processmentioning
confidence: 99%
See 3 more Smart Citations